Performing Surgery: Commonalities with Performers Outside Medicine - Kneebone, Roger L. (Frontiers in Psychology, 2016)
This paper argues for the inclusion of surgery within the canon of performance science. The world of medicine presents rich, complex but relatively under-researched sites of performance. Performative aspects of clinical practice are overshadowed by a focus on the processes and outcomes of medical care, such as diagnostic accuracy and the results of treatment. The primacy of this ‘clinical’ viewpoint - framed by clinical professionals as the application of medical knowledge - hides resonances with performance in other domains. Yet the language of performance is embedded in the culture of surgery - surgeons ‘perform’ operations, work in an operating ‘theatre’ and use ‘instruments’. This paper asks what might come into view if we take this performative language at face value and interrogate surgery from the perspective of performance science. It addresses the following questions: 1. To what extent and in what ways can surgical practice (both consultation and operation) be considered as performance? 2. How does comparison with two domains domains of non-surgical performance (close-up magic and puppetry) illuminate understanding of surgical practice as performance? 3. In what ways might including surgery within the canon of performance studies enrich the field of performance science? Two detailed case studies over 5 years with magicians (71.5 hours contact time) and puppeteers (50.5 hours contact time) identified performative aspects of surgical practice from the perspectives of professionals (as individuals or in groups) and audiences. Physical simulation provided a means for non-clinicians to access and experience elements of the surgical world, acting as a prompt for discussion. Thematic analysis was used to establish themes and sub-themes. Key themes were: 1) clinical consultation can be viewed as ‘close-up live performance with a very small audience’ and 2) operative surgery can be viewed as ‘reading bodies within a dextrous team’. These preliminary categories suggest a framework for systematic interrogation of surgery as a performative site and for further comparison with performance domains outside medicine.